Efficacy of zanubrutinib versus acalabrutinib for relapsed or refractory chronic lymphocytic leukemia (R/R CLL): a matching-adjusted indirect comparison (MAIC) - Mazyar Shadman; Jennifer R. Brown; Rhys Williams; Leyla Mohseninejad; Keri Yang; Pal Rakonczai; Nicole Lamanna; Sheng Xu; Aileen Cleary Cohen; Susan M. O’Brien; Alessandra Tedeschi; Constantine S. Tam (Therapeutic Advances in Medical Oncology, 2025)
Background: There are no head-to-head studies comparing the efficacy of the Bruton tyrosine kinase inhibitors, zanubrutinib and acalabrutinib, in relapsed or refractory chronic lymphocytic leukemia (R/R CLL). Objective: To compare the relative efficacy of zanubrutinib and acalabrutinib in R/R CLL using indirect treatment comparison. Design: An unanchored matching-adjusted indirect comparison (MAIC) was performed. Methods: Individual patient-level data from ALPINE (zanubrutinib) were reweighted using prognostic/effect-modifying variables to match aggregate data from ASCEND (acalabrutinib). MAIC outcomes included investigator-assessed progression-free survival (PFS-INV), overall survival (OS), and complete response (CR). Results: Post-matching, PFS-INV was improved significantly for zanubrutinib versus acalabrutinib (hazard ratio (HR) = 0.68 (95% confidence interval (CI): 0.46–0.99); p  = 0.0448) and OS showed a trend toward improvement for zanubrutinib (HR = 0.60; 95% CI: 0.35–1.02, p  = 0.0575). CR was significantly higher for zanubrutinib versus acalabrutinib (odds ratio = 2.90 (95% CI: 1.13–7.43); p   =  0.0270). Conclusion: Zanubrutinib was associated with a significant PFS-INV and CR advantage over acalabrutinib, with a trend toward improvement in OS.